Novel MEIOB variants cause primary ovarian insufficiency and non-obstructive azoospermia - Wang, Yurong; Liu, Ling; Tan, Chen; Meng, Guiquan; Meng, Lanlan; Nie, Hongchuan; Du, Juan; Lu, Guang-Xiu; Lin, Ge; He, Wen-Bin; Tan, Yue-Qiu (Frontiers in Genetics, 2022)
Background: Infertility is a global health concern. MEIOB has been found to be associated with premature ovarian insufficiency (POI) and non-obstructive azoospermia (NOA) , but its variants have not been reported in Chinese patients. The aim of this study was to identify the genetic aetiology of POI or NOA in three Han Chinese families. Methods: Whole-exome sequencing (WES) was used to identify candidate pathogenic variants in three consanguineous Chinese infertile families with POI or NOA. Sanger sequencing was performed to validate these variants in all the probands and their affected family members. In vitro functional analyses were performed to confirm the effects of these variants. Results: Two novel homozygous frameshift variants (c.258_259del and c.1072_1073del) and one novel homozygous nonsense variant (c.814C>T) in the MEIOB gene were identified in three consanguineous Han Chinese families. In vitro functional analyses revealed that these variants produced truncated proteins and affected their function. Conclusion: We identified three novel MEIOB loss-of-function variants in local Chinese patients for the first time and confirmed their pathogenicity using in vitro functional analyses. These results extend the mutation spectrum of the MEIOB gene and have important significance for genetic counselling in these families.